A research on mix-teaching method: characteristics of employment education teachers on employability of students in Chinese institutions - Wen, Guo; Qing, Xie (John Wiley & Sons, Inc., 2024)
Student employability (SE) is the foremost requirement for current university, especially in the current pandemic situation that business and industry enterprises require more capable employees to survive in a highly uncertain world. There are several characteristics of the teachers such as personalities and ability to use innovative technologies which influences the employability of the students in Chinese universities. Thus, this study investigates the impact of employment education teachers' qualities, such as personalities and the capacity to use new technologies, on SE in Chinese universities, with a particular emphasis on the moderating function of mix‐teaching methods. The research has employed the questionnaires to gather the data from the chosen respondents. The article also applied the smart‐PLS to test the hypotheses of the study. The results revealed that the employment education teachers' characteristics have a positive nexus with SE in Chinese universities. The research clearly shows that the mix‐teaching technique considerably partially mediates the features of employment education teachers and SE in Chinese universities. This research will aid policymakers in implementing guidelines aimed at increasing SE.